THE RELATIONSHIP OF KNOWLEDGE WITH HIV/AIDS PREVENTION BEHAVIORS IN STUDENTS AT SMK KARYA GUNA BHAKTI 1 BEKASI - Mania, Wilysa; Meliyana, Ernauli; Arabta M. Peraten Pelawi (Rena Cipta Mandiri, 2023)
Many teenagers and minors are already familiar with drugs, freesex, brawls, theft, and other negative or criminal acts that are contrary to the norms that exist in society and have problems with the law in Indonesia. HIV / AIDS is one of the most frightening diseases, because until now it has not found a cure, so people who have this disease arguably do not have a long life expectancy. This study aims to determine the relationship between knowledge and HIV / AIDS prevention behavior in students of SMK Karya Guna Bhakti 1 Bekasi. The research method used is quantitative with crossectional types of research. The population in this study was students of class XI TKR (Light Vehicle Engineering), TBSM (Motorcycle Business Engineering), and MM (MultiMedia) SMK Karya Guna Bhakti 1 Bekasi and a sample of 105 students. Data retrieval techniques using purposive sampling. Statistical test using chi square test with the results of respondents who have good knowledge as many as 82 students (78.1%) and respondents with positive behavior towards HIV / AIDS prevention as many as 77 respondents (73.3%) obtained p-value (0.001) < (0.05). There is a relationship between knowledge and HIV / AIDS prevention behavior in students of SMK Karya Guna Bhakti 1 Bekasi.